2017
DOI: 10.1093/rheumatology/kex287
|View full text |Cite
|
Sign up to set email alerts
|

Infrapatellar fat pad features in osteoarthritis: a histopathological and molecular study

Abstract: OA IFPs and synovial membranes are more inflamed, vascularized and fibrous compared with those of control patients (without OA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
154
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 139 publications
(185 citation statements)
references
References 35 publications
13
154
0
Order By: Relevance
“…In accordance to this, studies could show a proinflammatory cytokine profile in the IPFP, by detection of, for example, TNF‐α, VEGF (vascular endothelial growth factor) and IL‐6 . Favero et al found a different cytokine profile in the fat pad of osteoarthritic patients compared with a control group of an organic‐donor program. However, it has to be mentioned, that the donors of the control group had a mean age of 81 years, which makes the exclusion of osteoarthritic changes, even if there were no clinical symptoms known, quite difficult.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…In accordance to this, studies could show a proinflammatory cytokine profile in the IPFP, by detection of, for example, TNF‐α, VEGF (vascular endothelial growth factor) and IL‐6 . Favero et al found a different cytokine profile in the fat pad of osteoarthritic patients compared with a control group of an organic‐donor program. However, it has to be mentioned, that the donors of the control group had a mean age of 81 years, which makes the exclusion of osteoarthritic changes, even if there were no clinical symptoms known, quite difficult.…”
mentioning
confidence: 72%
“…Moreover, it seems, that the IPFP could be involved in the inflammatory reaction pathognomonic for OA, as in an animal model, the injection of arthritogenic factor led to synovitis of Hoffa's synovia, infiltration with neutrophils and mononuclear cells and fat necrosis . Recent studies have shown that also the IPFP secretes proinflammatory cytokines and may modulate the inflammatory processes contributing to the pathomechanism of knee OA . A higher gene expression of IL‐6 was found in mesenchymal stem cells from the fad pad of OA patients compared with a control group of patients with an ACL rupture .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the IFP of patients with OA undergoing total knee replacement, an increase of inflammatory infiltration, vascularization and thickness of the interlobular septa was found. At the same time the synovial membrane adjacent to IFP presented lymphocytic infiltration, hyperplasia and higher vascularization compared with healthy controls (Favero et al 2017). In fact, in an experimental model of OA, marked loss of adipocytes in IFP was associated with extensive synovial proliferation (SP) and subsynovial fibrosis (Clements et al 2009).…”
Section: Histopathologymentioning
confidence: 90%
“…In fact, considering the intra-articular location of the IFP, the metabolic properties of adipose tissue and the fact that the OA involves all articular tissues, it is likely that the IFP could also be involved in OA of the knee (Clockaerts et al 2010). Peculiar microscopic changes in OA IFP, such as thickening of interlobular septa, an increase in vascularization and the presence of inflammatory infiltrates, have been described (Favero et al 2017;Macchi et al 2017). Importantly, these changes have also been observed in the IFP adjacent synovial membrane, suggesting a possible cross-talk between these two structures (Eymard et al 2014), which may support a possible role of IFP in disease progression (Wenham & Conaghan, 2010;Sime et al 2017).…”
Section: Introductionmentioning
confidence: 99%